Different Oxytocin Responses to Acute Methamphetamine Treatment in Juvenile Female Rats Perinatally Exposed to Stress and/or Methamphetamine Administration - Holubová, Anna; Poništ, Silvester; Jurčovičová, Jana; Šlamberová, Romana (Frontiers in Physiology, 2019)
Methamphetamine (MA) is an addictive psychostimulant, often abused by drug addicted women during pregnancy. The offspring of drug-addicted mothers are often exposed to perinatal stressors. The present study examines the effect of perinatal stressors and drug exposure on plasma oxytocin (OXY) levels in female progeny. Rat mothers were divided into three groups according to drug treatment during pregnancy: intact controls (C); saline (SA, s.c., 1 ml/kg); MA (s.c., 5 mg/kg). Litters were divided into four groups according to postnatal stressors lasting from PD1 to 21: non-stressed controls (N); maternal separation (S); maternal cold-water stress (W); maternal separation plus cold-water stress (SW). On postnatal day 30, acute MA or SA were administrated 1 hour before the rats were sacrificed. Trunk blood was collected and plasma OXY was measured by specific ELISA after extraction. Our results showed that acute MA administration significantly increases plasma OXY levels in juvenile female rats; this effect was observed in prenatally intact rats only. Prenatal exposure of rats to mild stressor of daily SA injection prevented both acute MA induced OXY stimulation and also stress induced OXY inhibition. Although postnatal MA and stress exposure exert opposite effects on OXY release in juvenile rats, our data point out the modulatory role of prenatal mild stress in OXY response to postnatal stressors or MA treatment.